Solid pseudopapillary tumor: a rare neoplasm of the pancreas - Shuja, Asim (Oxford University Press, 2014)
Solid pseudopapillary tumor is a rare primary neoplasm of the pancreas that typically affects young women. It is a relatively a benign tumor, with a favorable prognosis. We here report a 27-year-old woman with solid pseudopapillary neoplasm, who presented with mild jaundice, mildly elevated liver function tests and right upper quadrant pain. Ultrasound was suggestive of hemorrhagic hepatic adenoma; however, on magnetic resonance imaging, a heterogenous mass was found in the head of pancreas. Endoscopic ultrasound-guided fine needle aspiration (FNA) revealed tumor cells with papillary architecture and immunohistochemical analysis showing cells positive for markers including beta-catenin, vimentin, alpha 1 antitrypsin etc. These findings were consistent with solid pseudopapillary neoplasm. The patient underwent pancreaticoduodenectomy. Post-surgical biopsy confirmed the FNA findings with tumor localized to the pancreas. The patient was not given any adjuvant therapy. She remained asymptomatic and showed no signs of disease after four months follow-up. It is important to differentiate this tumor from other pancreatic neoplasms, because this type is amenable to cure after complete surgical resection, even in cases with capsular invasion, unlike malignant tumors of the pancreas.